Safety, pharmacokinetics, and pharmacodynamics of a next‐generation subcutaneously administered coagulation factor IX variant, dalcinonacog alfa, in previously treated hemophilia B patients. (24th March 2021) - You, Chur Woo; Hong, Seung‐Beom; Kim, Suyeong; Shin, Ho‐Jin; Kim, Jin Seok; Han, Jung Woo; Kim, Soo‐Jeong; Kim, Do Young; Lee, Martin; Levy, Howard
Abstract: Background: Dalcinonacog alfa (DalcA), a next‐generation, recombinant human factor IX (FIX) variant, was developed using a rational design approach for increased procoagulant activity and longer duration of action to be administered subcutaneously (SC) for prophylaxis of hemophilia B bleeding episodes. Objectives: To investigate the safety, pharmacokinetics (PK), and pharmacodynamics (PD) of DalcA. Methods: This multicenter, phase 1/2a study (NCT03186677) was conducted in 11 males aged 12 to 65 years with severe hemophilia B. In cohort 1, subjects received intravenous (IV) 75 IU/kg BeneFIX and DalcA. Cohorts 2 and 3 had DalcA IV 75 IU/kg and SC 75 IU/kg or 150 IU/kg. Cohort 4 was omitted. Cohort 5 received daily SC 150 IU/kg DalcA for 6 days and cohort 6 received IV 75 IU/kg and daily SC 150 IU/kg DalcA for 9 days. Blood sampling was performed for chemistry, hematology, PK, PD, and anti‐drug antibody measurement. Subjects were monitored for safety endpoints for 30 days postdosing. Results: DalcA demonstrated a 24‐fold greater potency over BeneFIX and longer mean residence time (33.8 h). SC bioavailability 8.2% to 20.3%, beta half‐life 53.9 to 106.9 h and Tmax 24 to 48 h. A median 15.7% FIX activity level (interquartile range, 14.9%‐16.6%) was reached after 6 daily doses. Neutralizing antibodies to ISU304, but not wild‐type FIX, occurred in two cousins. Conclusions: The data demonstrated that DalcA achieved protective FIX activity levels between 11% and 18%, corresponding to a reduced chance of spontaneous bleeds. Based on the results, a phase 2b trial to assess the safety and efficacy of 28 daily SC doses of DalcA was performed.